Subunit Vaccine ESAT-6:c-di-AMP Delivered by Intranasal Route Elicits Immune Responses and Protects Against Mycobacterium tuberculosis Infection - Ning, Huanhuan; Zhang, Wei; Kang, Jian; Ding, Tianbing; Liang, Xuan; Lu, Yanzhi; Guo, Chengxuan; Sun, Wenjie; Wang, Huapeng; Bai, Yinlan; Shen, Lixin (Frontiers in Cellular and Infection Microbiology, 2021)
Tuberculosis (TB), caused by Mycobacterium tuberculosis (Mtb) infection, remains the most common cause of death from a single infectious disease. More safe and effective vaccines are necessary for preventing the prevalence of TB. In this study, a subunit vaccine of ESAT-6 formulated with c-di-AMP (ESAT-6:c-di-AMP) promoted mucosal and systemic immune responses in spleen and lung. ESAT-6:c-di-AMP inhibited the differentiations of CD8+ T cells as well as macrophages, but promoted the differentiations of ILCs in lung. The co-stimulation also enhanced inflammatory cytokines production in MH-S cells. It was first revealed that ESAT-6 and c-di-AMP regulated autophagy of macrophages in different stages, which together resulted in the inhibition of Mtb growth in macrophages during early infection. After Mtb infection, the level of ESAT-6-specific immune responses induced by ESAT-6:c-di-AMP dropped sharply. Finally, inoculation of ESAT-6:c-di-AMP led to significant reduction of bacterial burdens in lungs and spleens of immunized mice. Our results demonstrated that subunit vaccine ESAT-6:c-di-AMP could elicit innate and adaptive immune responses which provided protection against Mtb challenge, and c-di-AMP as a mucosal adjuvant could enhance immunogenicity of antigen, especially for innate immunity, which might be used for new mucosal vaccine against TB.